Association between undernutrition and language delay in children under 5 years old: a systematic review - Lulus Hardiyanti; Anindya Khairunnisa Zahra; Fara Azmiarrizqi; Amelia Nur Khasanah; Sheila Agustina; Ardiyuga Pratitapraya; Puguh Oktavian (Indonesian Journal of Biomedicine and Clinical Sciences, 2025)
In 2022, global statistics of the WHO (World Health Organization) reported 148.1 million children under 5 y.o. were too short for their age (stunting), 45.0 million were too thin for their height (wasting), and 37.0 million were too heavy for their height (overweight). Solving the problem of undernutrition is included in the second goal of the Sustainable Development Goals. Language skills are one of the important aspects of development in children. This study aimed to assess the association between undernutrition and language delay in children under 5 y.o. We searched PubMed, Scopus, and Web of Science for relevant studies published in 2014-2024. We identified studies that analyzed children under 5 y.o. with undernutrition and screenings for language delay, full-text, Indonesia, and English language studies, used cross-sectional study, case-control study, cohort study, and RCT study designs. The risk of bias was assessed using the ROBINS-E tool. There were 4,865 articles of search results in 3 databases consisting of PubMed, Web of Science, and Scopus. A total of 16 articles, including 11 cross-sectional studies and 5 cohorts, were analyzed. An association was observed between undernutrition and language delay. Other factors that significantly influenced language delay were paternal education, maternal education, and stimulation. Most studies report that the more severe the conditions of wasting, stunting and underweight will cause more severe conditions of language delay.